2000
DOI: 10.1002/14651858.cd001490
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate for treating exacerbations of acute asthma in the emergency department

Abstract: BackgroundTreatment of acute asthma is based on rapid reversal of bronchospasm and arresting airway inflammation. There is some evidence that intravenous magnesium can provide additional bronchodilation when given in conjunction with standard bronchodilating agents and corticosteroids. No systematic review of this literature has been completed on this topic. ObjectivesTo examine the effect of additional intravenous magnesium sulfate in patients with acute asthma managed in the emergency department. Search meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
140
0
18

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(159 citation statements)
references
References 32 publications
1
140
0
18
Order By: Relevance
“…From current data, magnesium sulfate is likely to improve bronchospasm and consequent clinical symptoms and reduce hospitalization in children with moderate to severe acute asthma when added to classic therapy. 121 Some studies [122][123][124] have shown clinical improvement in patients with severe asthma receiving intravenous magnesium infusion.…”
Section: Magnesium Sulfatementioning
confidence: 99%
“…From current data, magnesium sulfate is likely to improve bronchospasm and consequent clinical symptoms and reduce hospitalization in children with moderate to severe acute asthma when added to classic therapy. 121 Some studies [122][123][124] have shown clinical improvement in patients with severe asthma receiving intravenous magnesium infusion.…”
Section: Magnesium Sulfatementioning
confidence: 99%
“…Non-invaziv veya invaziv mekanik ventilasyon ihtiyacı olan hastalar çalışmaya dahil edilmemiştir. MS tedavisinin daha ağır astım ataklarında daha etkili olduğu bulgusundan yola çıkarak, daha ağır alevlenme ile başvuran ve MS tedavisinden daha fazla yarar görebilecek bir grup hastanın değerlendirilmemiş olabileceği söyle-nebilir (38). Akciğer volümlerinin ve solunum kas gücüne yönelik ölçümlerin yapılamamış olması da çalışmamızın diğer bir dezavantajıdır.…”
Section: Uygulanan öLçümler Ve Takip Parametreleriunclassified
“…[37,38] The response to magnesium appears to be best in patients who present with very severe illness (evidence C). [39][40][41] The benefits associated with the use of nebulised magnesium sulphate remain controversial. Nebulised magnesium sulphate (0.4 ml 50% MgSO 4 added to total volume of 4 ml nebuliser volume to achieve an isotonic solution) added to inhaled β 2 -agonists in the treatment of an acute asthma exacerbation has been shown to improve lung function in patients with severe asthma, with a trend towards fewer hospital admissions.…”
Section: Magnesium Sulphatementioning
confidence: 99%